Can we use hedonic pricing to estimate freight value of time? - Jérôme Massiani (Economics and Econometrics Research Institute (EERI), 2008)
In this article, we investigate the use of hedonic pricing method to measure freight value of time. We concentrate on the demand side of the freight market (that is shippers) and give a pre-cise definition to transport duration. We analyse the different temporal dimensions of freight transportation and examine how equilibrium forms on the freight market. This equilibrium is defined in reference cost and duration of the transport operations. Subsequently, we analyse how standard hedonic pricing technique has to be customised to be implemented on freight value of time. In a final section, we implement hedonic analysis on a data set consisting of ship-pers' interviews. We test different specifications and find information on the distribution of shippers' willingness to pay for transport time savings.
Keywords: R41; D61; 330; Hedonic pricing; freight value of time